PENGARUH NPF DAN CAR TERHADAP FINANCIAL DISTRESS PADA BANK UMUM SYARIAH DEVISA DAN NON-DEVISA - Farida Yanti, Reni; Abdul Fatah, Dian; Pratama, Rifaul (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2025)
This study aims to analyze the effect of Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) on Financial Distress in Foreign Exchange and Non-Foreign Exchange Islamic Commercial Banks in Indonesia. The study uses a quantitative approach with descriptive methods. The research sample was determined through purposive sampling, consisting of three Islamic Commercial Banks, namely PT Bank Syariah Indonesia Tbk, PT Bank Panin Dubai Syariah Tbk, and PT Bank BTPN Syariah Tbk, with a five-year research period and a total of 15 observation data. The data used are secondary data sourced from the banks' annual financial reports. Data analysis techniques include correlation coefficient analysis, determination coefficient analysis, multiple linear regression, t-test, and F-test using the SPSS program. The results of the study indicate that partially Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) have a positive and significant effect on Financial Distress, and simultaneously NPF and CAR have a significant effect on Financial Distress in Foreign Exchange and Non-Foreign Exchange Islamic Commercial Banks.